REPUBLIQUE DU TOGO (African Disability Rights Yearbook, 2021)
According to the 2010 General Population and Housing Census of Togo, the total population increased from 2 719 567 inhabitants in 1981 to 6 191 155 inhabitants in 2010; that is an average annual growth rate of 2,84 per cent. It is made up mainly of women (51,4 per cent) but also characterised by its extreme youth. Persons with disabilities represent 2,2 per cent. The State of Togo ratified the United Nations Convention on the Rights of Persons with Disabilities (CRPD) as well as its Optional Protocol on 1 March 2011. At the national level, the Togolese Constitution of 14 October 1992 directly or indirectly guarantees disability rights set out in the Convention through the provisions of articles 10, 11, 28 and 33. Law 2004-005 of 23 April 2004 on the social protection of persons with disabilities enriches this normative architecture. However, it should be noted that certain provisions of the law do not meet the requirements of the CRPD. To this end, a draft law on the promotion and protection of the rights of persons with disabilities is being prepared. At the institutional level, the implementation of the rights of people with disabilities is mainly ensured by the government under the aegis of the Ministry of Social Action, the Promotion of Women and Literacy and the Ministry of Human Rights and Relations with Institutions of the Republic in collaboration with the Togolese Federation of Associations of People with Disabilities (FETAPH). This active collaboration has contributed to the gradual improvement in the inclusion of disability concerns in public policies and programmes. This has made it possible to improve the care and inclusion of persons with disabilities through major actions, including the establishment of the Special Fund for persons with disabilities. However, despite a favourable context, among the challenges constituting major obstacles to the implementation of the rights of persons with disabilities in Togo, there are many obstacles relating to access to public buildings, insufficient consideration of the needs of workers with disabilities, persistent social stigma and the very low representation of persons with disabilities in elective office and decision-making positions. Making the law consistent with the CRPD should help remove these persistent obstacles.
Keywords: Togo; General Population and Housing Census; total population increased; persons with disabilities; social protection; promotion and protection of the rights; implementation of the rights